ANALISIS MANAJEMEN PRODUKSI PENULISAN BERITA DAN COPYWRITING DALAM INDUSTRI MEDIA DIGITAL DI PT. POJOK SATU INDONESIA - Shinta Sukmawati Khiran; Ika Sartika; Rr. Renny Soelistyowati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The digital media industry demands adaptive, creative, and relevant news writing and copywriting skills that meet the needs of the audience. The development of technology and changes in information consumption patterns have encouraged journalists and copywriters to master storytelling, Search Engine Optimization (SEO), and distribution strategies so that their content can compete in the rapid flow of information. This paper discusses the production process of news writing and copywriting skills based on internship experiences at PT Pojok Satu Indonesia. This paper was written using a qualitative approach with primary data in the form of observations, interviews, and documentations during the internship, as well as secondary data from books, journals, and other relevant sources. The result of the discussion show that writing effectiveness is influenced by an understanding of digital writing techniques, consistency in language style, and the demands of rapid content production. These findings emphasize the importance of strengthening professional skills in the digital media industry.